Uma avaliação do Programa Estadual de Distribuição Social De Gás (Vale Gás) no município de Fortaleza durante o período pandêmico (2020-2023) - Oliveira, Roberta Costa de (2024)
The pandemic caused by mpacto n disease (COVID-19) in 2020, in addition to exposing the deficiencies mpacto in health systems, deepened the hardships of social inequality, highlighting, above all, the difficulties in combating food insecurity. As a social right, the right to food calls for the adoption of public policies aimed at eradicating hunger and poverty that guarantee food and nutritional security. Thus, not being restricted to foodstuffs, the realization of this right encompasses the quality and nutritional value adequate for a healthy life, as well as the storage and preparation conditions of food that do not harm health, cause illness or damage. Therefore, this study assesses the impacts of Vale Gás Social on ensuring food security and alleviating poverty and extreme poverty in the state of Ceará between 2020 and 2023. To this end, the following specific objectives were established: a) To understand the human right to adequate food as a multisectoral and broad-ranging social right; b) To historically contextualize social inequality in the Brazilian State and the challenges accentuated by the pandemic; and; c) To analyze the implementation scenario of the Ceará State Social Gas Distribution Program (Vale Gás) and its contributions to food security in Fortaleza city. In this mpacto n, a qualitative approach is adopted using bibliographic and mpacto n research combined with the evaluative axes of the In-Depth Assessment. It was concluded that the program had a positive mpacto n the quality of life of the people benefiting from extreme poverty, bringing security and ease in cooking food